Penerapan Model Project Based Learning Untuk Meningkatkan Keterampilan Proses Sains Siswa SMPN 1 Makassar: Application of the Project Based Learning Model to Improve the Science Process Skills of SMPN 1 Makassar Students - Resty Desfita Sari, Resty Desfita Sari (Jurusan Pendidikan Teknik Elektro, 2025)
This article is a classroom action research that will examine the project based learning model to improve students' Science Process Skills (SPS). Initial observations showed low SPS, low SPS results also caused low student learning outcomes. The subjects of this study were students of class IX-3 SMPN 1 Makassar. The tools used in this study were scientific process skills observation sheets and student response sheets. Data analysis was carried out using quantitative descriptive techniques with percentages. The results of the study showed that the application of the project-based learning model was able to improve students' science process skills. This can be seen from the percentage of students' achievement of science process skills from cycle I to cycle II. Cycle I The average value was 69.1 with a fairly good category and in cycle II the average value was 89.0 with a very good category. This shows an increase in science process skills from cycle I to cycle II.